Development of Indirectly Driven Shock Tube Targets for Counter-Propagating Shear-Driven Kelvin-Helmholtz Experiments on the National Ignition Facility. (1st September 2016) - Capelli, D.; Schmidt, D. W.; Cardenas, T.; Rivera, G.; Randolph, R. B.; Fierro, F.; Merritt, E. C.; Flippo, K. A.; Doss, F. W.; Kline, J. L.
Abstract: The shear experiments are designed to investigate the transition to turbulence of the Kelvin-Helmholtz instability driven by counter-propagating shear flows. The shear targets for the National Ignition Facility (NIF) shear experiments consist of two hohlraums connected to both ends of a shock tube. The cylindrical shock tube is filled with two hemi-cylindrical CH foams separated by a metal tracer foil. On both ends, a thick gold half-moon–shaped D-plug is placed on opposite halves of the tube to create counter-propagating shock waves. The design is based on a smaller Omega shear target. While the basic NIF design has remained the same, details of the design have undergone several changes over the last 2 years and continue to evolve to improve the quality of the experimental results. Design changes include shock tube designs, tracer foil variations, transitioning to beryllium spool machining, and groove features inside of the tube. Details of how the targets are built including design, machining the parts, target assembly, and metrology are presented, as well as recent target developmental work to meet the needs of future experiments and to improve target assembly efficiency and accuracy.